2020
DOI: 10.7324/japs.2020.10811
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and optimization of Enalapril Maleate-loaded floating microsphere using Box–Behnken design: in vitro study

Abstract: The objective was to prepare an Enalapril Maleate (EnM)-loaded floating microsphere with minimum particle size, maximum drug loading, and drug entrapment efficiency. Formulations were prepared by varying drug-to-polymer ratio (A), solvent ratio (B), and stirring time (C). The solvent evaporation method was used to prepare the microsphere. "Box-Behnken's design" (3 factors × 3 levels) was utilized for optimization. The independent variables were polymerto-drug ratio (A), solvent ratio (B), and stirring time (C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…After 3 mo of storage, the percent drug content, percent entrapment efficiency, and percent drug release, percent mucoadhesion, and particle size (µm) of the chosen formulation (F18) were determined. The studies revealed that there no noticable change in drug content, entrapment efficiency, mucoadhesion, drug release and particle size after storage for 3 mo at 4±1 °C, 25±2 °C; 60±5% RH and 37±2 °C; 65±5% RH as reported by Bahadur K. V. et al, 2020 [12]. It was also revealed that formulation F18 stored at 4±1 °C showed maximum drug content of (65.32 %) followed by the storage at 25±2 °C; 60±5% RH and 37±2 °C; 65±5% RH conditions.…”
Section: In Vivo Pharmacodynamic Studysupporting
confidence: 52%
See 1 more Smart Citation
“…After 3 mo of storage, the percent drug content, percent entrapment efficiency, and percent drug release, percent mucoadhesion, and particle size (µm) of the chosen formulation (F18) were determined. The studies revealed that there no noticable change in drug content, entrapment efficiency, mucoadhesion, drug release and particle size after storage for 3 mo at 4±1 °C, 25±2 °C; 60±5% RH and 37±2 °C; 65±5% RH as reported by Bahadur K. V. et al, 2020 [12]. It was also revealed that formulation F18 stored at 4±1 °C showed maximum drug content of (65.32 %) followed by the storage at 25±2 °C; 60±5% RH and 37±2 °C; 65±5% RH conditions.…”
Section: In Vivo Pharmacodynamic Studysupporting
confidence: 52%
“…Twenty different runs have been undertaken, and the responses for each run were documented. The composition with the optimal outcomes was chosen for future research [12].…”
Section: Optimization Of Formulation By Central Composite Designmentioning
confidence: 99%
“…The kinetic study was performed to determine the mechanism of drug release from oating microspheres. The drug release data were plotted into the different kinetic models, such as zero order, rst order, higuchi and korsemeyer-peppas kinetics [29,31].…”
Section: Lag Timementioning
confidence: 99%
“…Microsphere drug delivery systems have been formulated by various techniques, including phase separation or precipitation, emulsion/solvent evaporation, and spraying, melt congeal /dispersion technique 7 . The principle of lipid microsphere preparation offers a simple and practical approach to achieve increased gastric residence time for the dosage form and controlled drug release 8 .…”
mentioning
confidence: 99%